Bioethical view of euthanasia in Colombia: Readings from the actors involved in the process - González Cortés, Jorge Hernán; Valencia Cano, Laura María; Arias Castrillón, Yesika Fernanda; Castaño Londoño, Mariana (Pensando Psicología, 2020)
Objective: To describe convergences and divergences between the perceptions of patients with terminal, chronic or degenerative diseases, family and health personnel of Manizales regarding the application and implications of euthanasia. Methodology: Mixed investigation, with concurrent triangulation design and with a sample made up of 45 participants selected through quota sampling. Results: Patients, relatives and health professionals converge in affirming that autonomy is the bioethical principle that guides the application of euthanasia, despite the fact that professionals favor greater knowledge of the principle of justice; At the same time, limited knowledge is concluded regarding the laws and sentences that govern euthanasia in Colombia. Value of the study: The study represents usefulness both for the participants to the extent that it will allow identifying the incidence of social and family beliefs in the application of euthanasia, and for hospital institutions by allowing them to inform themselves about the reasons that make health personnel participate in the process and the level of involvement to which they are exposed. Conclusions: Indicators of ignorance by health personnel, family members and patients with chronic, terminal or degenerative diseases regarding euthanasia care protocols persist, evidencing the need to qualify the ethical training processes for healthcare personnel, while the debate facing the procedure is permeated by issues regarding human rights, dignity and quality of life of the patient and their families.